VHDL Modeling Of Speech Recognition Using Neural Network - Teoh, Kung Yu (2005)
The usage of speech recognition has become common and important in the current society. The role of speech recognition has also been applied to critical tasks through software programming. This is slow and impractical to be applied to a simple system. In order to overcome this, this thesis look into implementation of isolated word recognition system in hardware using Very High Speed Integrated Hardware Description Language (VHDL).